ESTIMASI POPULASI KETAM KENARI (Birgus latro ) PULAU SIOMPU - Jahidin (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
Estimation of the Birgus latro population on the siompu island applied at the supralitora zona, that is the zona of A (north coastal supralitoral), the zona of B (east coastal supralitoral), the zona of C (south coastal supralitoral), and the zona of D (west coastal supralitoral). Objective study was presume of Birgus latro population and sex ratio on the Siompu Island. This research used capture recapture method. Analysis of the population estimation is use anticipation formula by Petersen while female and male ratio use descriptively analysis. Results of research showed that estimate value of population in each of the zona supralitoral area is unegual that is the zona of A is 7,5 or ± 8 individual, the zona of B is 10 individual, the zona of C is 14.4 or ± 14 individual, and the zona of D is 12 individual. Estimate value of the Birgus latro population size on the supralitoral zona of siompu island is 43.9 or ± 44 individual. Male and female ratio in each that; the zona of A is 4:3, the zona of B is 6:2 or 3:1, the zona of C is 9:3 or 3:1, and the zona of D is 8:1. Male and female ratio of Birgus latro at the supralitoral zona of Siompu Island is 27:9 or 3:1.